PERUBAHAN DISTRUPTION MELALUI RASIO KEUANGAN DAN FLUKTUASI NILAI TUKAR - yesa cahayaning ramadhani (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2021)
This study aims to examine and analyze the effect of changes in distruption through the effectiveness of financial ratios and the risk of exchange rate fluctuations. The population in this study are all retail companies listed on the Stock Exchange. The sampling technique was carried out using a purposive sampling technique, which is based on the following criteria: companies that published financial reports as of December 31 have been completed consecutively, especially in 2014 - 2018, companies that always use exchange rates in their operating companies sequentially during 2014 - 2018. The sample to be selected is the financial statements of Indonesian retail companies which are stated in Rupiah, the data obtained is in the form of secondary data from the Annual Stock Exchange Report. The research hypothesis was tested using multiple linear regression analysis techniques and Residual MRA. The results showed that: Proxy of profitability through gross profit margin has a positive and significant effect on free cash flow; Leverage that is proxied through the level of operating leverage does not have a significant positive effect on free cash flow; The activity ratio that proxies total asset turnover does not have a significant positive effect on free cash flow; The entry of the exchange rate was not able to significantly moderate the influence of the profitability structure and the ratio of activities to cash flows